Extended lactations to overcome reproduction problems in mountain low-input dairy systems - Pomiès D.; Fournier F.; Farruggia A. (Mountain pastures and livestock farming facing uncertainty: environmental, technical and socio-economic challenges, 2016)
With the end of milk quotas, dairy mountain farmers cannot compete with low-land farmers because of higher costs and lower productivity. So they have to maximize the use of local forages, reduce their inputs and make quality products like PDO cheeses. To study this new context, we designed since 2011 two low-input innovative farming systems at an INRA experimental farm (1100 m asl): 12 Holstein and 12 Montbéliarde cows in each; a short calving season (~77 days) before turning-out to pasture to superimpose lactation curve on grass growth; no concentrate or 4 kg/d during 200 days. Unfortunately, those systems led to poor reproductive performances, with only 35% of adult cows calving during the following season, without difference between systems or breeds. To overcome the low number of pregnant cows, we decided to extend of ~10 months the lactation of some non-pregnant cows (7 to 23 each year), in order to have always 24 lactating cows by system during summer. The 53 cows involved in extended lactations (~568 d) produced 70% more milk by lactation (8026 vs. 4715 kg) than cows with ‘standard’ lactations of 289 days, without significant difference between systems or breeds. In addition, these cows had better reproductive performances, with 79% of pregnant cows and 72% of calving the following spring. Even if these results must be completed by an economic study, extended lactations seem to be an interesting practice to reinforce the sustainability of seasonal low-input dairy mountain systems.
19. Meeting of the FAO-CIHEAM Mountain Pastures Subnetwork, 2016/06/14-16, Zaragoza (Spain)